Direct production of hydrogen-enriched syngas by calcium-catalyzed steam gasification of Shengli lignite/chars: Structural evolution. (18th March 2020) - Ban, Yanpeng; Liu, Quansheng; Zhou, Huacong; He, Runxia; Zhi, Keduan; Li, Na
Abstract: Calcium has been proved to be efficient for the catalytic steam gasification of lignite. In this study, we studied the steam gasification of lignite with Ca(OH)2 added by wet impregnation for to produce hydrogen. The effect of calcium on the microstructural evolution and char gasification behavior in the presence of steam were studied. The distribution of the gaseous products was examined by using fixed-bed micro reactor equipment for steam gasification. Partially gasified chars obtained at different temperatures (400, 500, 600, and 700 °C) in the gasification process were characterized by scanning electron microscopy coupled with energy dispersive spectroscopy, 13 C nuclear magnetic resonance, Fourier-transform infrared spectroscopy, and Raman spectroscopy. The results suggested that a "Ca-carboxylate-like structure" was formed due to the addition of calcium to lignite. This Ca-carboxylate-like structure increased the thermal stability of the original carboxylic structure in lignite. As a result, the calcium-added coal retained more oxygen-containing structures, formed more defects, and possessed significantly lower aromatic structures due to the formed Ca-complexes during steam gasification. Therefore, it can be inferred that the Ca-complexes in the lignite char increased the gasification reactivity of char. Highlights: Reduced gasification temperature, enhanced reactivity and H2 by adding calcium. Strongly changes of char texture under reaction state by added calcium. Indispensable effect of Ca-carboxylate evolution on the structure of lignite char. Dependence of gasification characteristics on structural evolution. Catalytic mechanism of gasification process on structural evolution.